Effects of aerobic and resistance exercises on circulating apelin-12 and apelin-36 concentrations in obese middle-aged women: a randomized controlled trial - Sun-Hwa Jang; Il-Young Paik; Jae-Hoon Ryu; Tae-Hyung Lee; Dae-Eun Kim (BMC, 2019)
Abstract Background The risk for obesity-related diseases increases with the prevalence of obesity. In obesity, adipokines secreted from adipose tissue induce inflammation, causing adverse effects. Recently, adipokines such as apelin, visfatin, and chemerin have been studied. Long-term resistance training improves health in middle-aged women by improving metabolic risk factors, body composition, and muscle strength. However, there is still a lack of evidence on the association of apelin concentration with different exercise types in middle-aged obese women This study aimed to investigate the effects of 8 weeks of aerobic and resistance exercises on apelin-12 and apelin-36 levels and thereby verify the effects of different exercise types in obese, middle-aged women. Methods Participants were middle-aged women aged 50-61 years, with no experience of systematic exercise in the last 6 months, and met the WHO obesity criteria for the Asia-Pacific region of waist circumference ≥ 80 cm and body fat percentage ≥ 30%. Subjects were selected and allocated to the aerobic exercise, resistance exercise, or no exercise group by block randomization. Body weight, body fat, and body mass index were measured by bioelectrical impedance analysis. Analysis of variance, the t-test, and Tukey's post-hoc test were performed. Results A total of 24 participants were selected with eight participants in each group. Both aerobic and resistance exercises were effective in altering the physical composition, showing significant decreases in weight, waist circumference, BMI, and body fat. The aerobic and resistance exercise group showed a significant, positive change in apelin-12 levels. Conclusions In obese individuals, aerobic and resistance exercise were effective in improving obesity and reducing blood apelin-12 concentration, which is closely correlated with indicators of metabolic syndrome. Future research should focus on comparing the response of apelin to exercise in obese subjects treated with only dietary control and the response in the obese subjects of different ages and sex. Trial registration No. 1040917-201,506-BR-153-04, Clinical Research Information Service (CRIS), Republic of Korea (05 October 2018, retrospectively registered).